(untitled) (Tesis Psicológica, 2021)
Objectives: This study examined visual and auditory processing of children with reading disabilities (RD) to determine whether they show an impaired ability to judge a reading-related process such as temporal order of events and clarify whether or not this deficit is linked to rapid processing deficit. Method: The performance of 16 children with RD was compared with the performance of children in two control groups – one for chronological age (CA) and one for the same reading level –, doing visual and auditory temporal order tasks, both with linguistic and non-linguistic stimuli with inter-stimuli-intervals of 50, 150, or 300 ms. Results: The RD group performance was lower than the performance of the CA group in tasks requiring auditory temporal order processing for linguistic and non-linguistic stimuli. Regarding visual tasks, the RD group performed worse than both control groups in processing non-linguistic stimuli. In general, performance in every group decreased with decreasing inter-stimulus-interval (ISIs), suggesting that children with RD do not have impairments in the speed of perceptual processing. Conclusions: The perceptual problems of children with RD are better explained by temporal order processing problems than by difficulties in rapid processing. Inclusion of temporal order processing tasks in the evaluation of children with RD is recommended.